Novel synthesis of nano-calcium carbonate (CaCO3)/polystyrene (PS) core-shell nanoparticles by atomized microemulsion technique and its effect on properties of polypropylene (PP) composites - Mishra, Satyendra; Chatterjee, Aniruddha; Singh, RajPal (Polymers for Advanced Technologies, 2011)
Calcium carbonate (CaCO3)/polystyrene (PS) nanoparticles (< 100 nm) with core-shell structure were synthesized by atomized microemulsion technique. The polymer chains were anchored onto the surface of nano-CaCO3 through triethoxyvinyl silane (TEVS) as a coupling agent. Ammonium persulfate (APS), sodium dodecyl sulfate (SDS) and n-pentanol were used as initiator, surfactant, and cosurfactant, respectively. Polymerization mechanism of core-shell latex particles was discussed. Encapsulation of nano-CaCO3 by PS was confirmed by using transmission electron microscope (TEM). Grafting percentage of core-shell particles was investigated by Thermogravimetric Analyzer (TGA). Nano-CaCO3/PS core-shell particles were characterized by Fourier transform infrared (FTIR) spectrophotometer and differential scanning calorimeter (DSC). The results of FTIR revealed existence of a strong interaction at the interface of nano-CaCO3 particle and PS, which implies that the polymer chains were successfully grafted onto the surface of nano-CaCO3 particle through the link of the coupling agent. In addition, TGA and DSC results indicated an enhancement of thermal stability of core-shell materials compared with the pure nano-PS. Nano-CaCO3/PS particles were blended with polypropylene (PP) matrix on Brabender Plastograph by melt process with different wt% of loading (i.e. 0.1-1 wt%). The interfacial adhesion between nano-CaCO3 particles and PP matrix was significantly improved when the nano-CaCO3 particles were grafted with PS, which led to increased thermal, rheological, and mechanical properties of (nano-CaCO3/PS)/PP composites. Scanning electron microscope (SEM) and atomic force microscope (AFM) images showed a perfect dispersion of the nano-CaCO3 particles in PP matrix. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: atomized microemulsion; core-shell nanoparticles; mechanical properties; polypropylene (PP); Rheological properties; Thermal properties